China catalyst : - Holloman, Dave M. (John Wiley&Son, Inc., 2013)
This book provides a current view of the growth and channels of modern retail now growing across the entire market. Considers the importance of understanding China's 'Digital World,' the unique online universe that is critical to reaching new consumers. Explores the current distribution as well as the supply chain trends and challenges that will help form the basis of a distribution strategy fundamental to market expansion. Leaders of Fortune 500 companies are beginning to realize that tapping the full growth opportunity in the China market is a requirement. Those companies that successfully make this transition will be among the winners in the next era of global competition. China Catalyst will enable you to be at the forefront in understanding this transition and capitalize on this historic shift.